Kajian Termodinamika Biogas Berbahan Dasar Kotoran Sapi: Luqman Budi Wicaksono, Ahmad Marzuki - Luqman Budi Wicaksono, Luqman Budi Wicaksono; Ahmad Marzuki, Ahmad Marzuki (Jurnal Fisika dan Aplikasinya, 2025)
Thermodynamics study on the process of liquid biogas is needed. The aim is to get information about: compressibility, expansivity, state equation, and biogas critical point. Research was done by taking compressibility and expansivity data. The data of compressibility is gained through the changing of volume when biogas is given a big pressure. The data of expansivity is gained through the changing of volume at higher temperature. The result of the experiment shows the value of compressibility is -1.9 × 10-5 m3 /cmHg and the value of expansivity is 7.3 × 10-2 m3 /K. The biogas state equation is ln AV/V = 7.3 × 10-2 m3 /K (T - T0 ) + 1.9 × 10-5 m3 /cmHg (P - P0 ).